(untitled) (Aporia, 2020)
The following essay is a survey of uses of hinge propositions in epistemological theories. I shall begin by looking at the sceptical paradox which is the main antagonist in Epistemology. I will then move on to look at the origins of the idea of hinge propositions, which had their root in late Wittgenstein. Finally I shall look at the two most prominent modern theories utilizing hinges; those of Crispin Wright and Michael Williams. In addition, I shall cover some of the main problems concerning these theories, and some brief possible responses.